Sensing Strategy Based on Carbon Quantum Dots Obtained from Riboflavin for the Identification of Pesticides - Casagrande-Denardin, J; Melo-Freire, R (Elsevier B.V., 2019)
In this work, a fluorescent sensing strategy was developed for identification of pesticides in food, which was obtained thought the interaction of carbon quantum dots (CQDs) and silver nanoparticles (AgNPs). The CQDs were synthesized from riboflavin according to an experimental design. On this basis, the most appropriate samples were selected and structurally characterized, where AgNPs efficiently quench the fluorescence of CQDs due a fluorescence resonance energy transfer (FRET). The CQDs was titrationed with AgNPs (Ag@PAA and Ag@bPEI), determining the best concentration of quenching (0.228 and 3.030 pmol.L−1, respectively). Furthermore, a strategy of sensing was developed in order to identify the pesticides propanyl, parathion, dimethoate, chlorpyrifos and pyrimicarb, which were also verified in real samples of rice, carrot, orange and pepper. The results were analyzed by linear discriminant analysis (LDA), obtaining different response patterns against pesticide concentrations, with confidence level of 95%. After that, assays were performed using lower concentrations of the analytes. It was verified that in pepper extract, the sensibility of the sensing strategy was 250 ng.mL−1. Therefore, the CQDs synthesized in this work may be considered a powerful tool to identify pesticides in food samples. © 2019 Elsevier B.V.